Analyses on the roller structure of equivalent honeycombs for forest harvester under impact loading. (15th April 2021) - Qu, Yunfei; Wang, Dian
Abstract: The roller honeycomb feeding roller (RHFR) of forest harvester in logging was raised for reducing damage to logs. The equivalent relationship of roller double V-wings honeycomb (RDWH) were proposed and analytically derived in the mass, platform stress and elastic modulus. The finite element models of RDWH with various cell densities under the equivalent relation were established. The mechanical properties, energy absorption characteristics, impact response, structural stability, structure efficiency and improvement performance efficiency of RDWH under compression impact were investigated in comparison with roller hexagonal honeycomb (RHH). The RDWHs with equivalent relationship had approximate mechanical properties under unit compression displacement. The RDWH, benefiting from the NPR enhancement phenomenon in deformation, possessed about multiple times of mechanical properties and energy absorption efficiency than RHH. The performance efficiency of RDWH related to cell densities and cell layers in "PVP" and "Bunching Phase" trend. The RHFR exceeded that of the steel feeding roller (SFR) with about 2 times in maximum contact area under the corresponding contact force. The phenomenon of "sequential increment" and "uprush stage" appeared in contact area of RHFR for Gi groups were recorded with relating of cell densities and cell layers, which provided significance on reducing damage to logs.